The civil responsibility of the oral and maxillofacial surgeon according to Brazilian Civil Law (Research, Society and Development, 2022)
The civil liability of health professionals (doctors, dentists, nurses, nursing technicians, etc.) has been an increasingly present topic in Brazilian courts. The main objective of this study was to discuss the civil liability of the dental surgeon, specialist in oral and maxillofacial surgery and traumatology. Discussions about the civil liability of health professionals are often controversial, usually based on the theory of guilt, that is, the presence of elements of culpability in the professional's actions. In this way, as a general rule, intent is excluded in cases of medical errors. In addition, the oral and maxillofacial surgeon, as a rule, is responsible for the type of obligation of means, which is the one where the professional does not assume the risk of a certain result, but the duty to act with responsibility, diligence and prudence, according to the techniques established in the scientific literature, committing to treat the patient in the best possible way, with caution and zeal. Liability for existing losses or damages can only be attributed to the point at which the presence of fault or intent is demonstrated.